2003
DOI: 10.1021/jf034758o
|View full text |Cite
|
Sign up to set email alerts
|

Histological Structures of Cooked Rice Grain

Abstract: Raw and cooked whole grain sections of milled, medium grain California rice were compared for gross histological and morphological features using fluorescence and scanning electron microscopy (SEM). Cooked and raw grains were compared and the differences were assessed by autofluorescence of the cell walls and correlating fluorescence to SEM images. Milled, raw grains contain fine cracks throughout the endosperm. Cooked grains have wider, more defined cracks, suggesting that they serve as channels for water mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 8 publications
5
42
0
2
Order By: Relevance
“…The examination of cross-sectional SEM micrographs showed that the gelatinized rice grain appeared to have a typical histological structure with cracks ( Figure 3A), as described by Dgawa et al (2003). Dgawa et al (2003) suggest that grain of cracks serve as channels for the flow of water into the grain during cooking.…”
Section: Internal Structure Of Gelatinized and Retrograded Rice Grainmentioning
confidence: 80%
See 3 more Smart Citations
“…The examination of cross-sectional SEM micrographs showed that the gelatinized rice grain appeared to have a typical histological structure with cracks ( Figure 3A), as described by Dgawa et al (2003). Dgawa et al (2003) suggest that grain of cracks serve as channels for the flow of water into the grain during cooking.…”
Section: Internal Structure Of Gelatinized and Retrograded Rice Grainmentioning
confidence: 80%
“…As a main dietary source of carbohydrates, rice plays an important role in energy requirements and nutrient intake (Ramesh et al, 2000;Dgawa et al, 2003;Park et al, 2012). Contrary to other grains, rice is usually consumed as a whole grain for the main meal (Ramesh et al, 2000;Dgawa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By definition, heterogeneous denotes variety and indicates nonuniformity. Ogawa et al (2003) showed that the morphology of the starch particles in the grain is made up of different sizes. Voids and microcracks also served as microchannels for moisture migration.…”
mentioning
confidence: 99%